Design of large beam beams with high level of asymmetry using the strut brace technique - Linaja García, Glenda Milagros (2020)
It studies the beams of great can’t, which are used to withstand large loads or for architectural conditions. This investigation consists in the determination of the design of a discontinuous beam in totality, both in load and in geometry, using the strut-pull technique, therefore, using bibliographic information of similar research works, the structural design of this beam, the technique is recommended by the Peruvian Standard E.060. Subsequently, modeling was carried out in the AbaqusCAE software to determine steel reinforcement efforts, percentage of damage parameters, Von Mises and Tresca efforts, percentage of cracks and crushing percentage, resulting in a good design for this type of structures, which was verified in the software where it has a good behavior, concluding that, for samples with considerable discontinuities it is recommended to use the Strut and Tie technique.